Two-Tier Wage Structures: Implications for Equity Theory - Martin, James E.; Peterson, Melanie M. (Academy of Management Journal, 1987)
This study is an application of equity theory to an examination of the effects of implementing a two-tier wage structure. Using data from 1,935 employees in retail stores, we assessed commitment to union and employer, perceived pay equity, and the union's perceived instrumentality regarding pay. Significant multivariate and univariate differences emerged for wage tier, part- or full-time status, and?among low-tier employees?work location. Results generally suggest that equity theory appears as a useful conceptual framework for examining two-tier wage structures.